Casos investigativos como uma metodologia para a mobilização do pensamento crítico no ensino de Química: uma análise sob a perspectiva da pesquisa de desenvolvimento - Silva, Adelma Talline (2022)
In Science Teaching for Basic Education, Scientific Literacy is discussed as a mediation for the construction of scientific knowledge and the development of Critical Thinking (CP). Several studies have been carried out on teaching strategies that are potentially favorable for the development of Critical Thinking. As another alternative, we can bring the use of Investigative Cases (CI) as a teaching proposal that promotes Scientific Literacy and CT capabilities. This research aimed to investigate how IC can be used, as a didactic strategy, to mobilize the capacities of Critical Thinking in Chemistry classes, in the perception of a group of teachers in initial training. This study was structured in Design Research, a research methodology under development that allows the projection of the production of teaching strategies in cyclical stages seeking to improve the material produced, which in the case of this research sought to answer the research question of how IC can be used as a didactic strategy, capable of mobilizing PC capacity in Chemistry classes. Thus, this research aimed at the production and validation of IC with a group of graduates, members of the Pedagogical Support Program for Graduates at School - PROLICE - Chemistry Nucleus - of the Federal University of Sergipe. With the methodological path structured in Design Research or development research, through a system of elaboration-validation-re-elaboration of IC, in which the successive validations, which were carried out during a training course, are configured as part of the process of generating knowledge about the material that is sought to be developed to meet a certain objective. Such validations took place through the analysis of the ICs elaborated, questionnaires, discussions about IC and CP and the production of an Investigative Teaching Sequence. The interpretation of the data from this validation process took place through the Content Analysis technique, as it allows making inferences about the feasibility and reformulations of the first prototype. Among some of the results achieved, it was observed that the essential elements for the elaboration of a good Investigative Case are relevant to understand and help the production of this didactic strategy, as well as it can be noted that from the procedures adopted in the research it was possible to observe indications of mobilization of capacities to “Focus an issue”; “Making and evaluating inductions”; “Decide on an action” and “Interact with others” from Critical Thinking. It was also identified that although the activities were designed to express these capacities of Critical Thinking, the activities express capacities in different areas.